Differences in injectable platelet-rich fibrin fraction of peripheral blood on the release of TGF-β1 and PDGF-AB - Suryono, Suryono; Danastri, Arifia Anindita (Faculty of Dentistry, Universitas Gadjah Mada, 2023)
Injectable platelet-rich fibrin (i-PRF) refers to second-generation platelet concentrate. In this study, the results of i-PRF centrifugation were fractionated into three layers: yellow i-PRF, buffy coat, and red i-PRF. Injectable platelet-rich fibrin fractions used in this study were yellow i-PRF, red i-PRF, and a mix of both. This study aimed to examine the level of growth factor release of transforming growth factor beta 1 (TGF-β1) and platelet-derived growth factor (PDGF) in yellow i-PRF, red i-PRF, and a mix of yellow i-PRF and red i-PRF with the ratio of 1:1. A total of 10 ml of peripheral blood from healthy female donors was centrifuged (at 700 rpm in 3 minutes) to obtain i-PRF and fractionated into three layers. The upper yellow layer was taken as yellow i-PRF, while the bottom red layer was taken as red i-PRF and was taken together with the middle layer (buffy coat). The release of TGF-β1 and PDGF in each of i-PRF fractionation method, i.e. yellow i-PRF, red i-PRF, and a mix of yellow i-PRF and red i-PRF with a ratio of 1:1 was measured with ELISA. The measurement was observed for 24 hours, 3 days, 7 days, 10 days, and 14 days. Data analysis used the two-way ANOVA test with a significance level of 0.05 and a post hoc LSD analysis to establish group significance. The group of yellow + red i-PRF significantly released PDGF-AB (p < 0.05). TGF-β1 was the highest of all groups on day 14. All groups showed an increase in growth factor release from time to time. The fractionation method of injectable platelet-rich fibrin affected the release of growth factor of PDGF-AB and TGF-β1. The highest release of PDGF-AB and TGF-β1 was found in the yellow + red i-PRF group with a ratio of 1:1 in the 14-day group, which was significant with the other two groups (p < 0.05).